Imam Az-Zarnuji's Thoughts (W. 591 H) in the Development of Islamic Education Learning Methodology - Farihin, Ahmad Nuril; Pahrurraji, Pahrurraji; Syarif, Fajar (Lembaga Yasin AlSys, 2025)
This study aims to identify the concept of learning methodology from Imam Az-Zarnūjī's perspective and analyze the form of Islamic education learning methodology development through the study of poems in the book Ta'līm al-Muta'allim. The researchers used a literature review with a qualitative research type through a descriptive analysis and content analysis approach. The data sources were excavated from primary and secondary data, while the data collection technique used observation and documentation. The study results indicate that the learning methodology in Imam Az-Zarnūjī's perspective conceptually is learning with a strong relational system between the concepts found, namely poems as learning strategies and methods. These strategies and techniques are seen in the three educational domains: cognitive, cognitive, affective, and psychomotor. Methodologically, the researchers found three learning strategies: the planning strategy, the at-ta'dībī strategy, and the continuity strategy. The researchers also found four learning methods as a real manifestation of the existing strategy: experimental, discussion, cooperation, and drill.